2015
DOI: 10.1371/journal.pone.0115342
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Calcium Phosphate Crystals on Calcified Human Aortic Vascular Smooth Muscle Cells and Potential Role of Magnesium

Abstract: BackgroundCardiovascular disease including vascular calcification (VC) remains the leading cause of death in patients suffering from chronic kidney disease (CKD). The process of VC seems likely to be a tightly regulated process where vascular smooth muscle cells are playing a key role rather than just a mere passive precipitation of calcium phosphate. Characterisation of the chemical and crystalline structure of VC was mainly led in patients or animal models with CKD. Likewise, Mg2+ was found to be protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 50 publications
3
45
1
Order By: Relevance
“…Magnesium was tested in this study and results confirmed its beneficial role in preventing the VC process. Although previous studies already established the beneficial role of Mg 2+ and demonstrated its ability to counteract the main calcification mediators [ 21 24 , 38 ], the precise intracellular mode of action of Mg 2+ remains elusive. Our data suggest that Mg 2+ is able to antagonize the Pi-induced decrease of 3 miRs (miR-30b, miR-133a, and miR-143) involved in mineralization processes or SMC phenotypic switch.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium was tested in this study and results confirmed its beneficial role in preventing the VC process. Although previous studies already established the beneficial role of Mg 2+ and demonstrated its ability to counteract the main calcification mediators [ 21 24 , 38 ], the precise intracellular mode of action of Mg 2+ remains elusive. Our data suggest that Mg 2+ is able to antagonize the Pi-induced decrease of 3 miRs (miR-30b, miR-133a, and miR-143) involved in mineralization processes or SMC phenotypic switch.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] We observed, however, that human aortic VSMCs exposed to high calcium, phosphate and magnesium concentrations in vitro stabilized CPA crystals without changing their structure and with no evidence of whitlockite crystal formation. 35 Based on this in vitro study, it is highly improbable that high magnesium concentrations alter CPA nucleation or growth by direct physicochemical interaction with the crystals. We hypothesize that the inhibitory effects of magnesium on vascular calcification occur via a cellmediated action.…”
Section: Vascular Calcificationmentioning
confidence: 98%
“…For years, people have focused on the effects of vascular implants on the proliferation and adhesion of vSMCs, but paid little attention to their roles in the vSMC phenotype modulation via altering vascular microenvironment. So far, there were a few of reports about vSMC calcification . Given the phenotypic flexibility of vSMCs, the contribution of the different vSMC phenotypes to atherosclerosis, and the rapid corrosion of magnesium, it is inevitable that the implanted Mg‐based stent materials would alter the vascular microenvironment and thus modulate the phenotypes of vSMCs at the treated vessels, and eventually affect the fate of the stent‐intervened atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%